Analysis of polymorphism of the APOBEC3G gene in HIV positive patients (Research, Society and Development, 2022)
Human immunodeficiency virus type 1 (HIV-1) is the etiologic agent of the current AIDS pandemic. Viral hepatitis B (HBV) and C (HCV) are highly prevalent in HIV-infected individuals. APOBEC3G (A3G) gene is a human genetic factor currently investigated in control of HIV-1 replication and progression of AIDS. Studies investigated its effect on HCV and HBV replication. APOBEC3G mediates changes that result in loss of genetic information and production of largely defective virions in the subsequent replication cycle. APOBEC3G gene variants have been described. The H186R variant may alter APOBEC3G function or levels of expression by altering its interaction with other proteins, or modifying its editing functions. This study aims to determine the frequency of the H186R polymorphism among 324 HIV-1 positive patients with and without co-infection by hepatitis B and C and analyze the correlation of the H186R genotypes with viral load of HIV-1. The results showed AA:AG:GG genotypes in the following proportion: 88.6%:9.3%:2.1% in HIV-1 mono-infected patients and 85.4%:12.4%:2.2% in HIV/HBV. The HIV/HCV co-infected patients and those with triple infection HIV/HBV/HCV showed only AA e AG genotypes, with frequencies of 90.1%:9.9% and 78.9%:21.1%, respectively. Patients with AA genotype had viral load of 37,969 ± 68,182 copies/ml and patients with AG genotype had viral load of 48,256 ± 54,186 copies/ml (p=0.180). Our results demonstrate that there is no correlation between the genotypes of APOBEC3G H186R polymorphism and viral load of HIV-1 in study population.